2022
DOI: 10.3390/math10030356
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Use Coordinate Based Meta-Analysis to Determine a Prior Distribution for Voxelwise Bayesian Second-Level fMRI Analysis

Abstract: Previous research showed that employing results from meta-analyses of relevant previous fMRI studies can improve the performance of voxelwise Bayesian second-level fMRI analysis. In this process, prior distributions for Bayesian analysis can be determined by information acquired from the meta-analyses. However, only image-based meta-analysis, which is not widely accessible to fMRI researchers due to the lack of shared statistical images, was tested in the previous study, so the applicability of the prior deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Third, potential employment of informed prior distributions could also be considered in follow-up studies. In fact, previous studies have shown that proper use of informed priors can improve model performance (Han, 2021c;2022). Future studies may employ informed priors based on results from the present study.…”
Section: Limitationsmentioning
confidence: 72%
“…Third, potential employment of informed prior distributions could also be considered in follow-up studies. In fact, previous studies have shown that proper use of informed priors can improve model performance (Han, 2021c;2022). Future studies may employ informed priors based on results from the present study.…”
Section: Limitationsmentioning
confidence: 72%
“…In fact, when Bayesian inference is conducted, the outcome is sensitive to prior beliefs (Sinharay and Stern 2002). Also, use of appropriate priors in Bayesian inference is a way to minimize a potential bias (Han 2022). Such a point suggests that setting up prior beliefs is very important to produce desirable outcomes at the end of the Bayesian learning process.…”
Section: Implications Of Learning Mechanism Based On Bayes Rule On Vi...mentioning
confidence: 99%